Unique presentation of blastic plasmacytoid dendritic cell neoplasm: a single‐center experience and literature review. Issue 4 (21st May 2014) - Paluri, Ravi; Nabell, Lisle; Borak, Samuel; Peker, Deniz
Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and highly aggressive hematological malignancy derived from precursors of plasmacytoid dendritic cells. Very few cases of BPDCN have been described with lack of skin manifestations at the time of diagnosis. Here we report two rare non‐cutaneous presentations of BPDCN without obvious skin lesions at our institution and also the literature review. Our first patient had a unique presentation of BPDCN confined to the sinonasal region with central nervous system involvement. The second patient we report is also atypical with regard to widespread disease that uncharacteristically spared the skin and bone marrow. BPDCN is a rare hematological malignancy involving immature plasmacytoid dendritic cells. It poses a diagnostic challenge requiring multidisciplinary approach to manage this disease. It is important to identify effective therapies for both cutaneous and non‐cutaneous presentations of BPDCN, since most cases are uniformly fatal with conventional chemotherapy alone. High‐dose induction therapy based on acute myeloid leukemia (AML) or acute lymphoblastic leukemia (ALL) regimens, to achieve complete remission followed by allo‐hematopoietic stem cell transplantation from related or unrelated donors is recommended to improve long‐term survival in these patients. Larger scale studies are warranted to understand the pathophysiology of the disease and the important prognostic indicators for optimal management. Copyright © 2014 John Wiley & Sons, Ltd.